USING PROGRAMMED LEARNING TECHNOLOGY IN ORGANIZING EXTRACURRICULAR LEARNING ACTIVITIES FOR GENERAL SECONDARY SCHOOL STUDENTS (International Conference on Economics, Finance, Banking and Management, 2025)
This article outlines the concept of programmed learning technology and its potential in educational practice. It presents suggestions and recommendations for applying this technology to organize extracurricular learning activities for students in general secondary schools.